Virtual Real Estate: New Trend or Global Scam? - N. I. Chyhryna; D. A. Pankov (Цифровая трансформация)
The paper studies the concept of «virtual real estate», the market of which is developing against the backdrop of the emergence of metaverses. The current trend in the development of the Internet involves the merging of gaming and social life, which forms a huge, rapidly growing economy of consumption of virtual goods. The main factor in adjusting the trend of digital development is the evolution of the interaction between the Internet and users, therefore, the article initially considered the features and distinctive features of web 1.0, web 2.0, web 3.0. The technical solutions that distinguish web 3.0 are shown, contributing to the expansion of opportunities for involving consumers in the virtual world and the formation of their own virtual economy. Further, the concept of «metaverse» is investigated, key characteristics are highlighted. It has been established that the metaverse is a hybrid of the virtual and physical worlds, creating a space for communication, life and work. The metaverse market is growing, which makes it attractive to investors, one of the ways to invest for which is to purchase virtual land and real estate. Virtual real estate cannot be touched, but it has value, increases in price, which makes it an attractive investment. The purchase of virtual real estate is carried out for real money. Virtual real estate is a piece of land in a virtual space on which it is possible to build objects and participate in the game. The article is an opportunity to understand what virtual real estate is – another global scam or an attractive investment.